Parties as governments in Eurasia, 1913-1991: nationalism, socialism, and development - Sablin, Ivan; Moniz-Bandeira, Egas (Routledge, Taylor & Francis Group, 2022)
The birth of Anfu China, East Asia's first party-state : towards a constitutional dictatorship of the gentry, 1916-1918 / Ernest Ming-tak Leung -- The Communist International : a party of parties confronting interwar internationalisms, 1920-1925 / Vsevolod Kritskiy -- The left opposition and the practices of parliamentarianism within the Bolshevik Party, 1923-1924 / Alexander V. Reznik -- Importing and exporting ideas of nationalism and state-building : the experience of Turkey's Republican People's Party, 1923-1950 / Paul Kubicek -- Competing with the marketplace : the Chinese Nationalist Party (KMT)'s Department of Propaganda and its political publishing program, 1924-1937 / Christopher A. Reed -- Aspirations for a mass political party in prewar imperial Japan : bureaucracy, the reformist right, and the creation of the Imperial Rule Assistance Association / Bruce Grover and Egas Moniz Bandeira -- Constitution-making in the informal Soviet empire in Eastern Europe, East Asia, and Inner Asia, 1945-1955 / Ivan Sablin -- Work teams, leading small groups, and the making of modern Chinese bureaucracy, 1929-1966 / Long Yang -- From revolutionary comrades to "mothers of the nation" : the Workers' Party of Korea's approach to the role of women in the 1950s-1960s / Natalia Matveeva -- The dawn before one-party dominance : South Korea's road to party politics under the Supreme Council for National Reconstruction, 1961-1963 / Kyonghee Lee -- The Yugoslav federation and the concept of one ruling party in its final hour / Jure Gašparič -- The vanguard's changing tempo : Communist Party of Czechoslovakia and government institutions, 1921-1990 / Adéla Gjuričová.
Includes bibliographical references and index
Keywords: Europe, Eastern -- Politics and government -- 20th century; Asia -- Politics and government -- 20th century; Aufsatzsammlung; Geschichte 1913-1991; Einparteiensystem; Eurasien